Prevalence Study of Sexually Transmitted Infections in Pre-Marital Couples Undergoing Pre-Marital Checkups at the Bantimurung Community Health Center - Nurdin Nurdin; Ridho Pratama; Muhammad Nur Irsal (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Sexually transmitted infections (STIs) are an important public health issue, especially among adults of reproductive age. Premarital screening plays a strategic role in the early detection of STIs to prevent transmission to partners and offspring. This study aims to determine the prevalence of sexually transmitted infections (STIs) and the characteristics of prospective brides and grooms who undergo premarital examinations at the Bantimurung Community Health Center (UPTD Puskesmas Bantimurung). This study used a descriptive design with a cross-sectional approach. The sample was determined using purposive sampling with a total of 64 respondents, and the sample size was calculated using the Lemeshow formula. This study was conducted from March 3 to June 2, 2025. Data were obtained through laboratory tests, including detection of HIV, syphilis, and hepatitis B using rapid diagnostic tests, as well as structured interviews regarding risk factors. The results showed that most respondents were aged 25–30 years (33 people or 52%), 20–24 years (21 people or 33%), above 30 years (9 people or 14%), and 19 years (1 person or 2%). Based on gender, there were 30 males (47%) and 34 females (53%). Laboratory results showed an STI prevalence of 1.6%, with one reactive syphilis case and 63 (98.4%) non-reactive cases, while all respondents were non-reactive for HIV and hepatitis B. It was concluded that the prevalence of STIs among prospective brides at the Bantimurung Community Health Center was low, with the main risk factors being low knowledge and risky sexual behavior. It is recommended that further research be conducted with a larger sample size and wider coverage area to obtain more representative results, as well as increased education about reproductive health and the importance of premarital checkups in preventing STIs.